Chapter 39: Sweet Corn Production in Florida - Eric H. Simonne; William M. Stall; Stephen M. Olson; Susan E. Webb; Timothy G. Taylor; Scott A. Smith; Richard N. Raid (EDIS)
This document is HS737, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.